Maintenance of balance between airway pressure and intracranial pressure in a patient with tracheal stenosis undergoing craniotomy: a case report - Güçlü,Çiğdem Yıldırım (2017)
Abstract Background and objectives: Tracheal stenosis is a rare but a life-threatening condition and anesthesia of a patient with tracheal stenosis is challenging for anesthesiologists. Maintaining stable hemodynamics and ventilation parameters are important issues in neuroanesthesia. Any increase in airway peak pressure and ETCO2 will result in increase in intracranial pressure which must be avoided during craniotomies. Tracheal stenosis could be a reason for increased airway pressure. Case report: We described a patient undergoing craniotomy with tracheal stenosis. Conclusion: Detailed preparation for intubation, to stabilize airway dynamics and to make the right decision for the surgery were important points. To maintain of a good balance between cerebral dynamics and airway dynamics were the pearls of this case.